Zoning of the Smolensk Region by the Degree of Potential Epidemic Hazard of Natural Tularemia Foci - V. P. Popov; T. V. Vatlina; M. V. Vorob’eva; D. S. Orlov; V. E. Bezsmertny (Проблемы особо опасных инфекций, 2017)
Objective of the study is to find areas characterized by different degree of potential epidemic hazard as regards tularemia in the territory of the Smolensk Region using GIS-technologies. Materials and methods. GIS-analysis of the archive data of the Center of Hygiene and Epidemiology in the Smolensk Region, obtained in the process of epizootiological and epidemiological monitoring (1941–2015) of enzootic as regards tularemia territories, as well as of Plague Control Center of the Rospotrebnadzor and literature sources was carried out. By means of Microsoft Excel created were the tables with the data on the sites of isolation (a total of 161) and residential areas (all in all 423), where patients with tularemia had been registered. Via Google Earth application, geographical coordinates of the base points (residential areas) were identified. Using GIS software package MapInfo Professional 10.5, a database was created, the layers on sites of human infections and agent isolation were obtained, and electronic map was generated. Results and discussion. Following GIS-analysis of epizootic and epidemic manifestations of natural tularemia foci in 1941–2015, differentiation of the areas by the degree of potential epidemic hazard was performed. It was established that the districts with high degree of potential epidemic hazard as regards tularemia and recurrence rate (more than 10–15 years) of its manifestations (culture isolation, human infection reports) occupy 30 % of the Smolensk Region. In addition, 42 areas of durable persistence (up to 60 years) of natural tularemia foci were spotted. The results revealed are the basis for the enhancement of epizootiological monitoring strategy and specifying the scope of prophylactic measures.